The Effectiveness of Using Smart Box Media on Children Raudhatul Athfal Amal Bakti Muslimin Marihat Bandar Simalungun North Sumatra - Wulandari, Dianty (Seulanga : Jurnal Pendidikan Anak, 2024)
This study examines the pedagogical effectiveness of a multi-sensory learning tool, the "smart box," in enhancing foundational academic skills among early learners at Raudhatul Athfal Amal Bakti Muslimin. Employing a case study methodology across three distinct classes, the research assessed the impact of the smart box on children's learning outcomes. The smart box is a tactile educational medium comprising three core components designed to foster early numeracy, literacy, and visual cognition through interactive engagement with numbers, letters, and images, respectively. Quantitative analysis of student performance revealed significant improvements, with average comprehension rates reaching 77.67% for the image-based component, 71.42% for the letter-recognition component, and 71.42% for the number-related component. The findings indicate that the smart box is a highly effective educational resource that positively influences student engagement and comprehension. This study concludes that such hands-on, multi-component media hold considerable potential as a valuable tool for enriching the learning environment in early childhood education.